Dressed or undressed? How to measure children's body weight in overweight surveillance?. Issue 12 (15th November 2013) - Censi, Laura; Spinelli, Angela; Roccaldo, Romana; Bevilacqua, Noemi; Lamberti, Anna; Angelini, Veronica; Nardone, Paola; Baglio, Giovanni
Abstract Objective To simplify body weight measurement and, particularly, to encourage children and their parents to participate in the Italian nutritional surveillance system OKkio alla SALUTE, children were measured with clothes and then the weight was corrected for the estimated weight of the clothes. In the present study we compared the children's weight measured in underwear, as recommended by the WHO (WWHO), with that obtained using the OKkio alla SALUTE protocol (WOK) and investigated how the latter affects the calculation of BMI and the assessment of overweight and obesity prevalence. Design Weight (twice in close sequence, with and without clothing) and height were measured. A checklist was used to describe the type of clothing worn. The estimated weight of clothing was subtracted from the WOK. BMI was calculated considering both values of weight and height; ponderal status was defined using both the International Obesity Task Force and WHO BMI cut-offs. Setting Thirty-seven third grade classes of thirteen primary schools in Rome and in two towns in the Lazio Region were recruited. Subjects The anthropometric measurements were taken on 524 children aged 8–9 years. Results The error in the calculation of BMI from WOK was very low, 0·005 kg/m2 (95 % CI −0·185, 0·195 kg/m2); the agreement between the percentages of overweight (not including obesity) and obese children calculated with the two methods was very close to 1 (κ = 0·98). Conclusions The error in BMI and in nutritional classification can be considered minor in a surveillance system for monitoring overweight/obesity, but eases the procedure for measuring children.